Clinical and gastro-duodenal histopathological features of enteropathy due to angiotensin II receptor blockers. Issue 10 (October 2021) - Costetti, Martina; Schiepatti, Annalisa; Fraticelli, Sara; Costa, Stefania; Maimaris, Stiliano; Lenti, Marco Vincenzo; Villani, Laura; Bianchi, Paola Ilaria; Di Sabatino, Antonio; Corazza, Gino Roberto; Vanoli, Alessandro; Biagi, Federico
Abstract: Background: Clinical elements differentiating enteropathy due to angiotensin II-receptor-blockers (ARBs-E) from coeliac disease (CD) are poorly defined. The histopathological features on duodenal and gastric biopsies in these patients still need to be investigated. Aims: To describe the clinical phenotype of ARBs-E in comparison to CD, and the histological findings of gastric and duodenal biopsies in ARBs-E. Methods: Clinical data of patients with ARBs-E and CD diagnosed between 2013 and 2020 were retrospectively reviewed. Baseline presenting symptoms and demographics were compared (Fisher's exact test and t -test). Gastric and duodenal histology in ARBs-E were revised by two independent pathologists. Results: 14 ARBs-E and 112 CD patients were enroled. Weight loss ( p < 0.01), acute onset of diarrhoea ( p < 0.01), hospitalization ( p < 0.01), and older age at diagnosis ( p < 0.01) were more common in ARBs-E. Duodenal histology in ARBs-E showed intraepithelial lymphocytosis in 71%, increased mucosal eosinophilic count in 57%, with preserved neuroendocrine, Paneth and goblet cells in all patients. Gastric histologic lesions at baseline, including lymphocytic gastritis, eosinophilic gastritis, chronic active gastritis, and metaplastic atrophic gastritis patterns were observed in 73% of patients, without Helicobacter pylori infection. Conclusions: ARBs-E showed a severe clinical phenotype, often requiring hospital admission. Gastric involvement at diagnosis is very common, and this could further support this diagnosis.